2009
DOI: 10.1016/j.jbmt.2008.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Altered motor control, posture and the Pilates method of exercise prescription

Abstract: Aims• To determine whether a basic set of Pilates exercises improves the efficiency of load transfer through the pelvis • To compare the effects on chronic, mild low back pain (LBP) symptoms of three slightly different Pilates based regimes MethodsA between subjects equivalent group experimental design was used -Independent variable: type of exercise training (three groups) -Dependent variables: efficient load transfer through the pelvis as measured by the stork test in weight bearing; low back pain symptoms A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
2
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 2 publications
0
42
2
10
Order By: Relevance
“…These studies recruited small sample sizes ranging from 28 to 53 participants and generally used scales and questionnaires that evaluated pain intensity and disability but did not address the specific functional capacity of the patient and global perceived effect. 1,2,5,9,18,19 This type of evaluation is representative of the improvement in nonspecific CLBP 35,36 and is proposed for this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies recruited small sample sizes ranging from 28 to 53 participants and generally used scales and questionnaires that evaluated pain intensity and disability but did not address the specific functional capacity of the patient and global perceived effect. 1,2,5,9,18,19 This type of evaluation is representative of the improvement in nonspecific CLBP 35,36 and is proposed for this study.…”
Section: Discussionmentioning
confidence: 99%
“…One of these trials observed that, in patients with LBP, Pilates-based exercises can improve body weight unloading during the gait cycle and reduce LBP in comparison with those not participating in the intervention 1 ; and another observed that Pilates-based exercises improve LBP when combined with exercises for posture training, such as hip flexion and eccentric contraction of the psoas. 18 When core strength and back performance were evaluated, the results were also satisfactory. 19 Recently, a systematic review included 3 dissertations and 4 clinical trials and concluded that the Pilates-based exercises are superior to minimal intervention for pain but not for disability at postintervention time point in the treatment of LBP.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It unites posture control, the body stability, and an improved motor development to the strengthening of these muscles and improve flexibility (31).…”
Section: Discussionmentioning
confidence: 99%
“…Although the Pilates method has been employed as part of fitness programs in the studios for a long time, it has only recently been shown to improve flexibility, abdominal muscular endurance, and static and dynamic balance in healthy people, and subsequently has become the subject of scientific research investigating its efficiency in patients with musculoskeletal diseases (35)(36)(37)(38)(39)(40). Chronic low back pain patients were reported to benefit from Pilates exercises (41).…”
Section: Discussionmentioning
confidence: 99%